2006
DOI: 10.1021/ac061309p
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Nitro Pesticides in Mainstream and Sidestream Cigarette Smoke Using Electron Monochromator-Mass Spectrometry

Abstract: In the third sentence of the first paragraph of the Experimental Section, the concentration of the analytes spotted on the TLC plates was actually 200 ng/µL, not 0.2 ng/µL. This statement should have read, "Standard stock solutions were prepared for TLC and ES-MS detection optimization by dissolving the dyes in methanol. A concentration of 200 ng/µL (450 pmol/µL for rhodamines B and 6G and 580 pmol/µL for rhodamine 123, respectively) was used for TLC spotting and a concentration of 0.2 ng/µL (450 fmol/µL for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A study performed by Dane et al (2006) confirmed flumetralin, pendimethalin, and trifluralin pesticides were previously detected in both mainstream and side stream cigarette butt. Pesticides have been shown to be more toxic to water fleas (D. magna and C. dubia) than to fish (P. promelas and A. affinis).…”
Section: Discussionmentioning
confidence: 59%
“…A study performed by Dane et al (2006) confirmed flumetralin, pendimethalin, and trifluralin pesticides were previously detected in both mainstream and side stream cigarette butt. Pesticides have been shown to be more toxic to water fleas (D. magna and C. dubia) than to fish (P. promelas and A. affinis).…”
Section: Discussionmentioning
confidence: 59%
“…arsenic, cadmium) and poison (i.e. ammonia, carbon monoxide, hydrogen cyanide, nicotine) (ATSDR, 2004;CDC, 2004 ;Dane et al, 2006;NIDA, 2006;UEPA, 2006;ATSDR, 2007).…”
Section: Harmful Chemical Ingredients In Cigarettesmentioning
confidence: 99%
“…Lower levels of estradiol are measured in newborns exposed to active tobacco during pregnancy. In addition, three pesticides of the dinitroaniline family have been detected in tobacco smoke (10). These three pesticides are known or suspected endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%